Psychological resilience and work engagement of Chinese nurses: a chain mediating model of career identity and quality of work life - Meng, Zhixing; Zhang, Lan; Zan, Haijing; Wang, Jingru (Frontiers in Psychology, 2023)
Aim: To investigate how nurses' psychological resilience affects their work engagement and the resulting pathways, namely, the intermediary effect of career identity and quality of work life.Background: Psychological resilience is the ability to adapt to new circumstances and overcome difficulties. Work engagement is a positive, perfect emotional and cognitive state in the work process, which has a positive effect on nurses' physical and mental health and career development. The importance of psychological resilience in nursing is growing in popularity. However, few studies have explored the relationship between psychological resilience and nurses' work engagement.